Caudal and Intravenous Anesthesia Without Airway Instrumentation for Laparoscopic Inguinal Hernia Repair in Infants: A Case Series. Issue 9 (July 2020) - Krishnan, Prakash; Whyte, Simon D.; Baird, Robert; Malherbe, Stephan
Abstract : We report a series of 20 neonates and infants (18 born preterm) who underwent laparoscopic inguinal hernia repair with caudal anesthesia, oxygen via nasal cannula, and intravenous anesthesia. Surgery was successful in all cases without airway instrumentation or intraoperative complications. Sedation was provided with dexmedetomidine, propofol, and remifentanil. Two patients had apnea in the following 24 hours. There were no unplanned intensive care admissions. Laparoscopy allowed unplanned bilateral repair in 2 cases. Caudal with intravenous anesthesia without airway instrumentation is a viable technique for laparoscopic inguinal hernia repair. Avoiding general endotracheal anesthesia may reduce perioperative complications and influence postoperative disposition.